Enabling methods for predictive digital twin in pavement performance modelling - Chen, Kun (2025)
Roads are vital assets and the backbone for any transportation system and support societal development by providing the foundation for constant mobility of goods and people. However, pavements are experiencing accelerated deterioration in most developed countries due to increased traffic volume and load, combined with rapidly changing climate. The existing reactive road asset management approach cannot keep up with the rate of pavement degradation, due to lack of condition data from infrequent inspection surveys and simple models that do not consider the factors influencing pavement performance holistically.